Probabilistic of in Situ Seismic Soil Liquefaction Potential Based on CPT-Data in Central Jakarta, Indonesia - Agung, Putera Agung Maha; Sultan, Ramlan; Idris, Muhammad; Sudjianto, Agus Tugas; Ahmad, Mustaffa Anjang; Hasan, Muhammad Fathur Rouf (International Journal of Sustainable Construction Engineering and Technology, 2023)
Jakarta City located at the northern part of Java Island has a potential liquefaction since there are many soil layers as a qualified as liquefaction susceptible, such as: silty sand and sand. The effects of liquefaction occurrence on saturated silty sand and sand during earthquakes can have potential to damage structure. A case history using CPT-data randomly taken from Central Jakarta region was compiled and back analyzed to investigated probability of liquefaction. The present study focuses on the probabilistic evaluation of liquefaction potential of this region, considering silty sand and sand layers related to CPT soundings. Silty sand was found as a thin layer or a lens between silty clay, silt and clay which was classified as a soft soil layer, and the sand layer is mostly found as a hard bottom layer. Normalization of tip CPT resistance (qc) corrected by an effective overburden stress was not only used to thick layer of silty sand and sand, but also it was applied to determine liquefaction potential existed as the “thin” layers. The silty sand and sand layers have a probability of liquefaction (PL) between 5 to 50% for magnitudes and distances of 500 years with PGA less than 0.42 gal.